Risk Factors for a Complicated Clinical Course Among Women Hospitalized With Pelvic Inflammatory Disease - Denise J. Jamieson; Ann Duerr; Milagros A. Macasaet; Herbert B. Peterson; Susan D. Hillis (Hindawi Limited, 2000)
The aim of this study was to identify factors ascertainable at initial presentation that predict a complicated clinical course in HIV-negative women hospitalized with pelvic inflammatory disease (PID). We used data from a cross-sectional study of women admitted for clinically diagnosed PID to a public hospital in New York City. A complicated clinical course was defined as undergoing surgery, being readmitted for PID, or having a prolonged hospital stay (≥ 14 days) but no surgery. Logistic regression was used to identify independent predictors of complications. In adjusted analyses, older age (≥35 years) was a risk factor for prolonged hospital stay (adjusted odds ratio [OR] = 3.9; 95% confidence interval [CI] = 1.3-11.6) and surgery (OR = 10.4; CI = 2.5-44.1); self-reported drug use was a risk factor for readmission for PID (OR = 7.7; CI = 1.4-41.1) and surgery (OR = 6.2; CI = 1.8-20.5). Older age and self-reported drug use appear to be independent risk factors for a complicated clinical course among women hospitalized with PID. Infect. Dis. Obstet. Gynecol. 8:88-93, 2000.